2013
DOI: 10.1021/es403574g
|View full text |Cite
|
Sign up to set email alerts
|

Induction and Coverage Times for Crude Oil Droplets Spreading on Air Bubbles

Abstract: The interactions between crude oil droplets and air bubbles were studied by the droplet-bubble micromanipulator technique. Eight crude oils were investigated, and some aspects of the involved mechanisms were discussed. The induction time was measured for air bubbles approaching crude oil droplets in different aqueous phases. Distinct differences were observed in the presence and absence of salts, which showed the importance of long-ranged electrostatic repulsive forces on thin-film stability. The results also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…In this work it was demonstrated that the amount, type, and surface affinity of water-soluble components in synthetic produced water were influenced by pH (reflecting pressure differences) of the aqueous solutions. Previously it was shown that water-soluble crude oil components prolonged the drainage time of the aqueous film between bubbles and drops, 24 and subsequently this reduced the removal efficiency of dispersed oil from produced water during gas flotation. 25 Consequently, it seems reasonable to anticipate that conditions giving rise to differences in surface pressure can influence the extent of oil removal during gas flotation.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work it was demonstrated that the amount, type, and surface affinity of water-soluble components in synthetic produced water were influenced by pH (reflecting pressure differences) of the aqueous solutions. Previously it was shown that water-soluble crude oil components prolonged the drainage time of the aqueous film between bubbles and drops, 24 and subsequently this reduced the removal efficiency of dispersed oil from produced water during gas flotation. 25 Consequently, it seems reasonable to anticipate that conditions giving rise to differences in surface pressure can influence the extent of oil removal during gas flotation.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…Furthermore, the drainage and rupture of the thin aqueous film formed upon the close approach of a single bubble and a single crude oil drop were studied in a drop-bubble micromanipulator system. 24 It was shown that the adsorption of hydrocarbons onto gas bubbles increased the drainage time of the film between bubbles and drops and thereby influenced the attachment between bubbles and drops. It was also shown in both laboratory and pilot scale flotation studies that the adsorption of the water-soluble crude oil components onto bubble surfaces reduced the removal efficiency of dispersed oil from water by gas flotation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the experimental set-up and methodology are further described by Eftekhardadkhah and Oye [14]. The experimental set-up applied by Eftekhardadkhah and Oye [14] is motivated by the work by Won et al [15]. The type of raw data obtained with the micromanipulator is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The collision and coalescence of two bubbles or droplets and the formation of a dimple, bridge and film rupture can be evaluated with external high‐speed cameras . Therefore, both droplets can be attached to cannulas and brought in contact which allows for a detailed analysis of the film drainage and development of the liquid bridge during coalescence , . The collision of a rising or falling particle with a particle fixed by a cannula has the advantage that the relative collision velocity as well as the effect of impact location can be analyzed and used to achieve information on the coalescence efficiency (Fig.…”
Section: Single Particle Characterizationmentioning
confidence: 99%